"The Caravaggio Within" Nan Goldin's Gina. (4th May 2017) - Leask, Ian
Abstract : This article offers a reading of Nan Goldin's 1991 photo "Gina at Bruce's dinner party, NYC", giving particular attention to the presence within it of a reproduction of Caravaggio's 1597 "Bacchus". It considers some similarities and differences between the two images and, drawing on Kierkegaard's problematizing of the possibility of repetition, suggests that the presence of "Bacchus" within "Gina" questions any uncritical assumption of "origin" or even re-presentation. It also suggests that, when we consider the wider oeuvres of both artists together, the "impossible repetition" that Gina enacts becomes more than a general point about representation and takes on an altogether queerer significance.